Flow measurement and monitoring using orifice plates - Papadopoulos, Christos E. (Cranfield University, 1996)
The orifice meter is still commonly used for natural gas measurement despite its many limitations. Considerable efforts in recent years have resulted in improved knowledge of factors such as installation effects and the value of discharge coefficient but a serious problem still remains with the measurement of differential pressure since, when line static pressures are as high as 200 bar, differential pressures of 500mbar have to be measured. Furthermore, the flow is never absolutely steady and the performance of the pressure transducers under such conditions is not yet fully understood. This thesis demonstrates the need to apply modern signal processing and analysis techniques to enhance the performance of process instrumentation systems. The use of two static pressure transducers of resonance type upstream and downstream the orifice meter, with a high frequency response, can offer the ability, by using spectral analysis and spectrum estimation methods, to extract additional information regarding the meter’s performance as well as diagnostic information about the whole process plant. It also demonstrates a method to check and, at the same time, to safeguard the flow information obtained from an orifice meter with the use of a third pressure transducer upstream of a Mitsubishi flow conditioner. Furthemore, information about the performance of the package orifice - conditioner using the discharge coefficient (Cd) and the amplitude spectrum from the three pressure transducers can be obtained.